Information Aggregation in Democratic Mechanisms - Volker Britz; Hans Gersbach (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine whether and how democratic procedures can achieve socially desirable public good provision in the presence of profound uncertainty about the benefits of public goods, i.e., when citizens are able to identify the distribution of benefits only if they aggregate their private information. Some members of the society, however, are harmed by socially desirable policies and aim at manipulating information aggregation by misrepresenting their private information. We show that information can be aggregated and a socially desirable policy can be implemented under a new class of democratic mechanisms involving a sample group. These mechanisms reflect the principles of liberal democracy, are procedurally efficient, and involve a conditional tax privilege of sample group members. This tax treatment motivates sample group members to reveal their private information truthfully before voting takes place. Depending on the distance between two feasible public good levels, the optimal mechanism involves either one or two voting rounds. We show that procedural efficiency cannot be achieved by communication among all citizens prior to voting. Finally, we outline several applications of the mechanism.
Keywords: D62; D72; H40; 330; democratic mechanisms; polling; sampling; public goods; voting; information aggregation